EXPLORING EFL STUDENTS’ PERSPECTIVES ON THE USE OF WATTPAD IN ENHANCING READING COMPREHENSION AT TADULAKO UNIVERSITY - Maya Syafirah Lamataya; Afrilia Anggreni; Moh. Abraham Akbar Eisenring; Anjar Kusuma Dewi (Tadulako University, 2026)
In the digital era, online platforms have become popular learning resources, especially for English as a Foreign Language (EFL) students. This study aims to explore students’ perspectives regarding the use of Wattpad, specifically focusing on their practices and challenges in enhancing reading comprehension at Tadulako University. This research employed a descriptive qualitative design. Data were collected through semi-structured interviews with seven students of the English Education Study Program who actively use Wattpad to read English texts. The data were analyzed using thematic analysis. The findings revealed two major themes: perceived benefits and encountered challenges. The results showed that students perceived Wattpad positively as it increased their reading motivation, enriched their vocabulary, improved their reading comprehension, and encouraged the use of active reading strategies such as rereading and using contextual clues. However, students also encountered several challenges, including difficulties in understanding unfamiliar vocabulary and complex grammar, interpreting implied meanings, comprehending informal language or slang, and dealing with distractions such as notifications and reading fatigue. This study implies that Wattpad serves as a valuable supplementary learning medium that supports extensive reading practice. Nevertheless, guidance and appropriate reading strategies are still required to optimize its benefits and overcome the existing limitations.